Improving Mindanao Agro-Industrial Competitiveness through Better Logistics and Connectivity - World Bank Group (World Bank, Washington, DC, 2020)
Despite being the largest food producer of the country, Mindanao remains Philippines’ poorest region. At the heart of Mindanao’s high poverty rate is the region’s weak ability to transform its natural advantage into a competitive one in domestic and foreign markets. This report examines the key constraints faced by Mindanao agricultural and manufacturing producers along the supply chains. For agricultural products, vegetables and cacao were chosen as illustration of the typical constraints faced along different value chains. Vegetables is a smallholder crop consumed domestically with a relatively short supply chain composed of producers, consolidators, and primary consumers. This short supply chain reflects the domestic market focus and limited extent of processing Cacao, on the other hand, has a longer supply chain extending to export markets. Compared to vegetables, cacao requires an additional layer of processing (from wet beans to dry fermented beans to processing for chocolate) before it can reach its final markets.